Bicuspid Valve Sizing for Transcatheter Aortic Valve Implantation: The Missing Link - Costa, Giulia; Angelillis, Marco; Petronio, Anna Sonia (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter aortic valve implantation (TAVI) is a well-recognized and established therapy for severe aortic stenosis, with expanding indications toward younger patients with low surgical risk profile. As bicuspid aortic valve (BAV) affects 1–2% of the population, it may be speculated that an increasing number of patients with degenerated BAV may eventually need TAVI during the course of the disease. On the other hand, BAV represents a challenge due to its peculiar anatomical features and the lack of consensus on the optimal sizing strategy. The aim of this paper is to review the peculiar aspects of BAV and to discuss and compare the currently available sizing methods. Special attention is given to the role of pre-procedural imaging, mostly with multislice computed tomography, and to the aspects that operators should evaluate in order to ensure an optimal procedural planning and avoid procedural-related complications.